Atividades biológicas de amostras semi-purificadas das folhas da Eplingiella fruticosa Salzm. ex. Benth - Souza, Jesica Batista de (2018)
Medicinal plants produce secondary metabolites with defense and survival functions in their habitat that are also useful as therapeutics. Eplingiella fruticosa (Lamiaceae) or “alecrim do vaqueiro” has been widely used by the population to treat fever, bronchitis, pains, infections, etc. It presents antimicrobial, antioxidant, larvicidal and other properties. The process of isolating or semi-purifying compounds increases the chances of finding bioactive phytochemicals, which may be at low concentrations in the extract. In this sense, chloroform extract (CE) of the leaves of E. fruticosa was semi-purified by flesh chromatography and classical liquid chromatography, and 29 semi-isolates were obtained. These semi-isolates were investigated for antioxidant, antimicrobial, larvicidal and cytotoxic activities. Phytochemical analysis revealed the presence of flavonoids, saponins and xanthones. The antioxidant activity against 2,2-diphenyl-1-picryl-hydrazil resulted in a strong activity in the methanolic subfraction (MS) with effective concentration (EC50) <50 mg. mL-1 and weak activity in CE and Group 23 (G23) EC50 > 100 mg.mL Their Total phenolics (FT), total flavonoids (FLT) and total flavonols (FLAVT) were quantified by spectrometric methods. The values obtained from all samples had an FT content higher than 100 mg.g-1 and were statistically similar, although the FLT and FLAVT values stood out in the CE. MS at 500 mg.mL-1 in the broth macrodilution test was effective against S. aureus, however, no sample (1 mg.mL-1 ) inhibited bacterial growth in the disk diffusion test. Experiments using Aedes aegypti larvae (L3) showed three subfractions with larvicidal effects, as follows: Group 18 (G18) presented a lethal concentrations (LC50) of 371 and 253 ppm in 24 and 48h, respectively, in the same way, chloroform subfraction (CS) presented LC50 of 815 and 752 ppm. After 48h, The MS presented a mortality rate of 93 ± 4.4, suggesting prolonged effect. In the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, CE, CS, ethyl acetate subfraction and MS samples in 1.56 to 12 mg.mL-1 concentrations did not decrease the viability of the human endothelial cells EA.hy926.